Utilization of tofu industrial waste treatment using bentonite - Mustamina Maulani; Bayu Satiyawira; Asri Nugrahanti; Mohammad Apriniyadi; Zakiah D. Nurfajrin; Henry Young; M. Kemal Disaputra (Community Empowerment, 2021)
Seamanan District, West Jakarta has a tofu industrial center which is managed by the primary Indonesian tofu production cooperative (which will be used as an educational tourism area. This is caused by wastewater from the tofu industry which does not carry out processing before being discharged into water bodies. Departing from the existing problems, the community service team conducted counseling to tofu industry person and the surrounding community regarding the urgency of wastewater treatment and how to overcome it. Based on laboratory studies, the wastewater treatment of the Seamanan tofu industry using bentonite and PAC resulted in a TSS removal of 53% and a TDS reduction of 95%. In addition, the BOD and COD values can decrease significantly, namely BOD by 87% and COD by 84%. This shows that the wastewater treatment of the Seamanan tofu industry has reached the quality standard of the Minister of Environment Regulation 5/2014, with the raw materials used being economical and environmentally friendly.